Mesoporous Silica‐Stabilized Ceria Antioxidants for Enhancing PEMFC Durability - Yeongseop Lee; Seong Hoon Kwak; Sangwon Kim; Hae Jung Son; Jin Young Kim; Ho Young Kim; Sang Hoon Joo (ChemElectroChem)
Enhancing the durability of polymer electrolyte membrane fuel cells (PEMFCs) is critical for advancing a hydrogen‐powered clean energy future. A major obstacle to improving PEMFC durability is reactive oxygen species (ROS) that deteriorate PEMFC performance by oxidizing membrane electrode assembly (MEA). While CeOx‐based nanomaterials are widely used as antioxidants, they often undergo decline in efficacy by their nanostructure deformation, hampering stable PEMFC operation. Here, mesoporous silica nanoparticles (MSNs) are reported as a stabilizer for antioxidants, effectively alleviating the CeOx disintegration. MSNs facilitate the formation of uniformly dispersed CeOx nanoparticles smaller than 2 nm having abundant oxygen vacancies and high proportion of Ce(III) oxidation states. The well‐defined mesoporous structure of MSNs effectively confines CeOx in the internal voids and prevents CeOx agglomeration, thereby exhibiting sustained antioxidation efficacy within the Pt/C‐based electrodes. Importantly, CeOx/MSN mitigates the MEA degradation, retaining 95% of PEMFC performance even after 100 h durability tests under the ROS‐rich environment.